2021
DOI: 10.1038/s41467-021-25150-0
|View full text |Cite
|
Sign up to set email alerts
|

Theta-phase dependent neuronal coding during sequence learning in human single neurons

Abstract: The ability to maintain a sequence of items in memory is a fundamental cognitive function. In the rodent hippocampus, the representation of sequentially organized spatial locations is reflected by the phase of action potentials relative to the theta oscillation (phase precession). We investigated whether the timing of neuronal activity relative to the theta brain oscillation also reflects sequence order in the medial temporal lobe of humans. We used a task in which human participants learned a fixed sequence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…Finally, we note that TPB naturally accounts for contiguity effects (i.e., if item n from a sequence in a free recall paradigm is recalled, then contiguous items at locations n - 1 and n + 1 are likely to be recalled next; Healey et al, 2019 ); and particularly the asymmetric nature of contiguity effects (the item at location n + 1 is more likely to be recalled than the item at location n - 1). Indeed, in TPB, items are preferentially “replayed” in the order in which they appeared, and this has been observed empirically ( Reddy et al, 2015 , 2021 ; Kok et al, 2017 ; Blom et al, 2020 ; Senoussi et al, 2020a ). However, a long list of benchmark phenomena relating to the contiguity effect have been reported (e.g., 34 phenomena by Healey et al, 2019 ), and we do not claim that we can explain them all based on time-based binding; nor, indeed, that time-based binding is responsible for all of them.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, we note that TPB naturally accounts for contiguity effects (i.e., if item n from a sequence in a free recall paradigm is recalled, then contiguous items at locations n - 1 and n + 1 are likely to be recalled next; Healey et al, 2019 ); and particularly the asymmetric nature of contiguity effects (the item at location n + 1 is more likely to be recalled than the item at location n - 1). Indeed, in TPB, items are preferentially “replayed” in the order in which they appeared, and this has been observed empirically ( Reddy et al, 2015 , 2021 ; Kok et al, 2017 ; Blom et al, 2020 ; Senoussi et al, 2020a ). However, a long list of benchmark phenomena relating to the contiguity effect have been reported (e.g., 34 phenomena by Healey et al, 2019 ), and we do not claim that we can explain them all based on time-based binding; nor, indeed, that time-based binding is responsible for all of them.…”
Section: Discussionmentioning
confidence: 73%
“…This work is consistent with other recent findings demonstrating that neurons in rat primary visual and parietal cortex can encode sensory and non-sensory factors related to movement, reward history, and decision making 3 . Similarly, a recent study on sequential memory in humans found that both strongly-tuned and weakly-tuned neurons recorded from the medial temporal lobe participated in theta-phase-locked encoding of sequence stimuli 30 . A previous study on working memory in primate prefrontal cortex also revealed that non-selective neurons can contribute to optimal ensemble encoding 18 , consistent with our own finding that mixed ensembles of classically and non-classically responsive cells improved encoding of task variables 15 .…”
Section: Introductionmentioning
confidence: 85%
“…Recent research has shown the existence of Time cells [ 60 ], which are elements of the Temporal Difference Algorithm. Another aspect that might play a role in the temporal inferences is the phenomenon of Phase precession [ 61 ], which is also related to the activity of time cells. Moreover, some authors have highlighted how Phase precession can facilitate STDP [ 62 ].…”
Section: Discussionmentioning
confidence: 99%